KEPADATAN MEGABENTOS PADA EKOSISTEM TERUMBU KARANG DI PERAIRAN DESA PERLANG BANGKA TENGAH, BANGKA BELITUNG - Arham Hafidh Akbar; Sudirman Adibrata; Wahyu Adi (Akuatik: Jurnal Sumberdaya Perairan, 2019)
This study aims to analyze the density of megabenthos in coral reef ecosystems in the waters of Perlang Village. This research was conducted in November 2019 in the waters of Perlang Village with the megabentos data collection method using the Bentos Belt Transect (BBT) method based on COREMAP CTI LIPI (2017) with 5 data collection stations. The results found 603 individuals consisting of 9 species from 4 megabenthos families in coral reef ecosystems. Species found at the study site are Diadema setosum, Diadema antillarium (Familli Deadematidae), Drupella cornus, Drupella rugosa (Family Murcidae), Trochus sp, Trochus conus, Tectus pyramis (Family Trochidae), Tridacna gigas, and Tridacna maxima (Family Tridacnidae) . The highest attendance percentage of all stations was obtained by Diadema setosum of 47.93% (289 people). Percentage of live coral cover from 5 observation stations ranged from 57.44% - 91.78%. Observation pensions that received the highest percentage of cover values ​​were at pension 2 with 91.78% in the very good category.